Gastrointestinal Findings in the Largest Series of Patients With Hereditary Biallelic Mismatch Repair Deficiency Syndrome: Report from the International Consortium. (February 2016) - Aronson, Melyssa; Gallinger, Steven; Cohen, Zane; Cohen, Shlomi; Dvir, Rina; Elhasid, Ronit; Baris, Hagit N; Kariv, Revital; Druker, Harriet; Chan, Helen; Ling, Simon C; Kortan, Paul; et al.
Abstract : Objectives: Hereditary biallelic mismatch repair deficiency (BMMRD) is caused by biallelic mutations in the mismatch repair (MMR) genes and manifests features of neurofibromatosis type 1, gastrointestinal (GI) polyposis, and GI, brain, and hematological cancers. This is the first study to characterize the GI phenotype in BMMRD using both retrospective and prospective surveillance data. Methods: The International BMMRD Consortium was created to collect information on BMMRD families referred from around the world. All patients had germline biallelic MMR mutations or lack of MMR protein staining in normal and tumor tissue. GI screening data were obtained through medical records with annual updates. Results: Thirty‐five individuals from seven countries were identified with BMMRD. GI data were available on 24 of 33 individuals (73%) of screening age, totaling 53 person‐years. The youngest age of colonic adenomas was 7, and small bowel adenoma was 11. Eight patients had 19 colorectal adenocarcinomas (CRC; median age 16.7 years, range 8–25), and 11 of 18 (61%) CRC were distal to the splenic flexure. Eleven patients had 15 colorectal surgeries (median 14 years, range 9–25). Four patients had five small bowel adenocarcinomas (SBC; median 18 years, range 11–33). Two CRC and two SBC were detected during surveillance within 6–11 months and 9–16 months, respectively, of last consecutive endoscopy. No patient undergoing surveillance died of a GI malignancy. Familial clustering of GI cancer was observed. Conclusions: The prevalence and penetrance of GI neoplasia in children with BMMRD is high, with rapid development of carcinoma. Colorectal and small bowel surveillance should commence at ages 3–5 and 8 years, respectively.